Epidemiology of ticks submitted from human hosts in Alberta, Canada (2000–2019). Issue 1 (31st December 2022) - Kanji, Jamil N.; Isaac, Abraam; Gregson, Daniel; Mierzejewski, Monika; Shpeley, Danny; Tomlin, Pauline; Groeschel, Michael; Lindsay, L. Robbin; Lachance, Lisa; Kowalewska-Grochowska, Kinga
ABSTRACT : The geographic range and occurrence of tick species is dynamic. This has important public health implications due to important tick species that can transmit pathogens. This study presents a retrospective review of tick genera recovered from humans and submitted for identification in Alberta, Canada, over a 19-year period. The total number of ticks and proportion of genera were analyzed over time. Molecular testing for a number of pathogens associated with Ixodes scapularis and I. pacificus was conducted. A total of 2, 358 ticks were submitted between 2000 and 2019, with 98.6% being acquired in Alberta. The number of ticks submitted increased significantly over time ( p < 0.0001). Dermacentor ticks were the most abundant genus, followed by Ixodes and Amblyomma . There was a significant decrease in the proportion of Dermacentor ticks between 2013 and 2019 ( p = 0.02), with a corresponding increase in the proportion of Ixodes ticks over the same time ( p = 0.04). No statistically significant change in seasonality was identified. Borrelia burgdorferi was detected in 8/76 (10.5%; 95% CI 5.4–19.4%) of all I. scapularis and I. pacificus ticks submitted. This translated to a B. burgdorferi positivity of 0.35% (95% CI 0.15–0.68%) among all ticks received. Dermacentor species (especially D. andersoni ) remains the most common tick feeding on humans in Alberta. Small numbers of vector species (including I. scapularis/pacificus ) are encountered annually over widely separated geographic areas in the province. The risk of exposure to tick-borne pathogens (e.g. Lyme disease) in Alberta remains low.